EVOLUTION OF PLACOID INFLAMMATORY LESIONS OF TUBERCULOUS SERPIGINOUS-LIKE CHOROIDITIS ON OPTICAL COHERENCE TOMOGRAPHY (OCT) AND BLUE AUTOFLUORESCENCE (BAF) - Zafar, Fahad; Bibi, Hafsa; Khan, Saad (Journal of Ayub Medical College Abbottabad, 2025)
Mycobacterium tuberculosis infection can affect the eyes, causing Serpiginous-like choroiditis (SLC) characterized by multifocal choroidal lesions at the level of Retinal Pigment Epithelium (RPE) that coalesce into a serpiginous pattern. It is managed with antitubercular treatment. On the other hand, Serpiginous Choroiditis (SC) is a chronic recurrent inflammatory disorder affecting the RPE layer with choriocapillaries as the primary target, and is managed with immunosuppressants. Differentiating SLC from SC is very important, since treating SLC with immunosuppressants can have devastating consequences for a TB-infected patient. We present a case of Tuberculous Serpiginous-like choroiditis in a 22-year-old male describing the evolution of placoid inflammatory lesion of the posterior pole. In addition, the role of BAF imaging in the management of the disease along with the correlation of BAF and OCT image findings has also been discussed.